A Validated Rubric for Scoring Learning Goals - Tai M. Lockspeiser; Patricia A. Schmitter; J. Lindsey Lane; Janice L. Hanson; Adam A. Rosenberg (Association of American Medical Colleges, 2013)
Abstract Introduction Creation of learning goals is an essential component of lifelong learning. In order to be effective, learning goals must be well crafted. No tool currently exists to assess the quality of learning goals. Methods We created a scoring rubric with four criteria designed to assess the quality of learning goals written by learners in health professions education. This rubric can be used both as a summative evaluation of a learner's goal-writing skills and as a means of providing feedback to improve written goals. The rubric is based on the ISMART (important, specific, measurable, accountability, realistic, time line) mnemonic for high-quality learning goals that identifies key aspects of successful goals. The final rubric includes four criteria, each with descriptive anchors that are scored from 0 to 3. The four criteria are specific goal, important goal, realistic multisource plan, and measureable outcome. This resource includes the scoring rubric, a worksheet to guide learners in the creation of high-quality learning goals, and detailed instructions for using the scoring rubric, including example goals to score as part of rater training. Results As far as we know, this is the only scoring rubric for learning goals or learning plans designed specifically with medical education in mind. We have used the scoring rubric with pediatric residents over 3 years, and it has provided a foundation for improving the quality of goals written by residents. With these improved goals, we have been better able to individualize residents' clinical experiences. Discussion Although most of our work using the scoring rubric has been with residents, we are beginning to implement it with medical students and in different contexts, such as with specific educational sessions or different rotations in the medical school and residency, showing that it is applicable to all levels of learners.